(untitled) (ARQUISUR Revista, 2021)
After a year of the first national legal provision of social isolation, we reflect on the impact of this on the growth and evolution operated in the conglomerate of Gran San Salvador de Jujuy. The objective of this research is to identify the forms of growth during 2020, compare them with previous years and detect if there are changes that are related to the context of pandemic. Through the analysis of satellite images we investigate the transformations in the agglomerate, we observe the areas that developed, the new expansions and the consolidations produced. In parallel, the promotions offered during the course of the year are researched in media, which, in turn, are verified in interviews with real estate developers. This allows us to conclude that the disruptive changes imposed by the health crisis, on the one hand, pose limitations and condition the actions of the population, and on the other, creates the strategic conditions to promote "informal" urban actions, both from the aptitude of their suitability as urban land and from the point of view of the administrative legal framework.